Advanced approaches to calculate recovery length and force redistribution in semi-parallel wire cables with broken wires. (15th January 2017) - Yu, Yujie; Chen, Zhihua; Liu, Hongbo
Highlights: Two advanced simplified approaches are proposed for semi-parallel wire cable. The theoretical model considers symmetric construction and extrusion transfer characteristic. The FEM approach employ beam element and spring element to simulate wire, contact and friction. Symmetric, asymmetric and multi-wire break conditions are all studied. Recovery length is influenced by sheath wrapped force, twist angle, and position of break wire. Abstract: Two simplified models, including a theoretical approach and a finite element method (FEM) model, are proposed to calculate recovery length and study the force redistribution mechanism in a semi-parallel wire cable with broken wires. In the advanced theoretical model, the symmetrical construction and extrusion stress transfer characteristic of the semi-parallel wire cable are considered. The clench effect of the polyethylene sheath and the prestressed helical wire are considered in the derivation. The simplified FEM model can exhibit mechanical performance at both wire and cable levels. It uses helically placed beam elements to simulate twisted wires, divergently arranged rigid beam elements at the wire cross section to simulate extrusion effect, and nonlinear spring elements to consider the contact and friction between the helical wires. Results show that the recovery length is influenced by the compaction effect of wrapped sheath, as well as the twist angle and position of the broken wire. Under the symmetrical break condition, the recovery lengths calculated using the two methods are in a good agreement with each other, and force redistribution mainly results from the friction effect. Under the asymmetrical break condition, however, force redistribution is dominated by the induced unbalanced moment.